2009
DOI: 10.1590/s0102-67202009000300001
|View full text |Cite
|
Sign up to set email alerts
|

Análise de custos entre a raquianestesia e a anestesia venosa com propofol associada ao bloqueio perianal local em operações anorretais

Abstract: INTRODUÇÃOAs doenças orificiais, como exemplo, as hemorróidas, são muito comuns na população geral. Estima-se que cerca de 5% da população adulta nos Estados Unidos é afetada por tais doenças 9 . Elas podem ser tratadas de forma conservadora, todavia, o procedimento cirúrgico é necessário e imperativo em muitos casos.A Sociedade Americana de Cirurgiões de Cólon e Reto, em seus protocolos práticos, autoriza a realização dos procedimentos cirúrgicos anorretais em regime ambulatorial em centros especializados com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Kotze et al demonstrated, in a similar study, reduced utilization time of the operating room in patients submitted to surgeries with combined anesthesia 6 . In the same study, published later, the overall costs were similar when comparing spinal and combined anesthesia 21 . However, in these four studies, the analysis was of direct and indirect costs.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Kotze et al demonstrated, in a similar study, reduced utilization time of the operating room in patients submitted to surgeries with combined anesthesia 6 . In the same study, published later, the overall costs were similar when comparing spinal and combined anesthesia 21 . However, in these four studies, the analysis was of direct and indirect costs.…”
Section: Discussionsupporting
confidence: 53%
“…The experience acquired in some years with this anesthetic technique, combined with a good relationship with the anesthesiology service, shows that the selection of combined anesthesia is more suitable to most patients. In addition, the service study group on this theme showed equivalent overall costs of the procedures, not only regarding the anesthetic materials, when comparing the two techniques 6,21 . At the final decision on the technique selected for the service procedures, indirect costs were also taken into account (shorter time in the operating room and hospitalization, among others), as well as the additional clinical benefits to the patient from the significant reduction of complications (mainly urinary retention and cephalalgia).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation